Signet Ring Cell Carcinoma of the Colon in Young Adults: A Case Report and Literature Review - Farida Abi Farraj; Hadi Sabbagh; Tarek Aridi; Najla Fakhruddin; Fadi Farhat (Case Reports in Oncological Medicine)
Colorectal cancer (CRC), one of the leading causes of cancer-related deaths, presents with challenging features related to its diagnosis and management. The incidence of CRC in the adolescent and young adult (AYA) population has increased over the past couple of decades despite the decline in the overall occurrence of CRC in the general population. Signet ring cell carcinoma is one of the rare histopathologic subtypes of CRC; however, it is more prevalent in AYA patients than in older adults and presents with unconventional histologic characteristics, a distinct clinical behavior, and a poor prognosis. We report a case of a primary signet ring cell adenocarcinoma of the ascending colon in a 19-year-old male who presented with unusual signs and symptoms and was diagnosed with stage IVA (T4a N0 M1, with peritoneal seeding). The unusual presentation and location of the tumor in this case warrant further investigation.